Khorana score and histotype predicts incidence of early venous thromboembolism in non-Hodgkin lymphomas - Santi, Roberto Mario; Ceccarelli, Manuela; Bernocco, Elisa; Monagheddu, Chiara; Evangelista, Andrea; Valeri, Federica; Monaco, Federico; Vitolo, Umberto; Cortelazzo, Sergio; Cabras, Maria Giuseppina; Spina, Michele; Baldini, Luca; Boccomini, Carola; Chiappella, Annalisa; Bari, Alessia; Luminari, Stefano; Visco, Carlo; Calabrese, Marco; Limberti, Giulia; Levis, Alessandro; Contino, Laura; Ciccone, Giovannino; Ladetto, Marco (Thrombosis and Haemostasis, 2017)
Current data suggests that the risk of venous thromboembolism (VTE) in patients with non-Hodgkin lymphoma (NHL) is comparable to that observed in patients with solid tumours, although more robust confirmatory analyses are required. With that in mind, we investigated the occurrence of VTE in a pooled analysis of 12 “Fondazione Italiana Linfomi” (FIL) prospective clinical studies. Specifically, we wished to assess the cumulative incidence of VTE in NHL patients, evaluate the predictive value of the Khorana Score (KS), and identify other potential risk factors for VTEs. Data for VTE occurrence were retrieved from study databases and pharmacovigilance reports. Our analysis includes 1717 patients from 12 prospective phase II and III trials, including newly diagnosed NHL. We observed 53 VTEs (any grade) in 46 patients, with 20 severe VTEs in 17 patients. The cumulative incidences for „all-grade” or grade ≥3 VTEs were 2.9% (95% CI: 2.1–3.8) and 1.1% (95% CI: 0.6–1.6), respectively. KS categories were positively associated with the risk of VTE of any grade, and with severe events (i. e. grade ≥3; Gray’s test p-values = 0.048 and 0.012, respectively). Among NHL patients, those with diffuse large B-cell lymphoma (DLBCL) showed a greater risk of (any grade) VTE (HR: 3.42, 95% CI: 1.32–8.84, p-value = 0.011). Our study indicates that 1) VTE is a relevant complication for NHL patients, 2) KS is predictive of VTE events and 3) DLBCL histotype is an independent risk factor for VTE incidence, for which preventative interventions could be considered.Supplementary Material to this article is available at www.thrombosis-online.com.
Keywords: Venous thromboembolism; non-Hodgkin lymphoma; Khorana Score